Analysis of existing international policy evidence in public health genomics: mapping exercise - Elena V. Syurina; Tobias Schulte in den Bäumen; Frans J.M. Feron; Angela Brand (SAGE Publishing, 2012)
Background. In the last decades we have seen a constant growth in the fields of science related to the use of genome-based health information. However, there is a gap between basic science research and the Public Health everyday practice. For a successful introduction of genome-based technologies policy actions on the international level are needed. This work represents the initial stage of the PHGEN II (Public Health Genomics European Network II) project. In order to prepare a base for bridging genomics and Public Health, an inventory study of the existing legislative base dealing with controversies of genome-based knowledge was conducted. The work results in the mapping of the most and the least legislatively covered areas and some preliminary conclusions about the existing gaps. Design and Methods. The collection of the evidence-based policies was done through the PHGEN II project. The mapping covered the meta-level (international, European general guidelines). The expert opinion of the partners of the project was required to reflect on and grade the collected evidence. Results. An analysis of the evidence was made by the area of coverage: using the list of important policy areas for successful introduction of genome-based technologies into Public Health and the Public Health Genomics Wheel (originally Public Health Wheel developed by Institute of Medicine). Conclusions. Severe inequalities in coverage of important issues of Public Health Genomics were found. The most attention was paid to clinical utility and clinical validity of the screening and the protection of human subjects. Important areas such as trade agreements, Public Health Genomics literacy, insurance issues, behaviour modification in response to genomics results etc. were paid less attention to. For the successful adoption of new technologies on the Public Health level the focus should be not only on the translation to clinical practice, but the translation from bench to Public Health policy and back. Coherent and consistent coverage of all aspects of the translation of genome based information and technologies is of outmost importance.